The Moderating Role of Information Sharing on The Relationship Between Lean Supply Chain and Supply Chain Performance: A Conceptual Framework - Susan Sabah Abdulameer; Noorulsadiqin Azbiya Yaacob (International Journal of Supply Chain Management, 2020)
This study aims to propose a framework for integrating information sharing (IS) into lean supply chain (LSC) to improving supply chain performance (SCP). This paper reviewed the studies published in the supply chain and going deep in LSC and its impact on SCP and disclosure of other relevant factors that play a significant role in enhancing the relationship such as IS. Also, it developed a conceptual framework to explain the moderating role of IS. This paper confirmed from previous studies that the results of the relationship between LSC and SCP are inconclusive. In other words, several empirical studies demonstrated there is a significant and positive relationship between LSC and SCP. In contrast, other studies found there is no significant relationship. Hence, the inconsistency in the results of previous studies leads to the need for moderating variable to enhance the relationship between LSC and SCP. Thus, the results of the study indicate a crucial moderating role for IS. This paper focuses on bridging the gap of IS as a moderator between LSC and SCP, as well as determining the common objective of LSC and IS which is improving SCP.